The Symbolic Meaning’s of the Mamminaraje’ Commemoration Tradition of the Bugis Bone Tribe Community - A. Rahmat Hidayat (Journal of Indonesian Islamic Studies, 2024)
This article discusses the symbolic meaning of the tradition of celebrating Isra' Mi'raj of the Bugis Bone Tribe community called mamminaraje'. The purpose of this study is to analyze and unravel the symbolic meaning of the mamminaraje' tradition which contains several sacred activities. The method used in this study is qualitative which is intended by the author to obtain descriptive data from the mamminaraje' tradition. Data is obtained from a combination of field research and library research. The results showed that the mamminaraje' tradition is the tradition of Isra' Mi'raj carried out by the Bugis Bone Tribe community. Some of the series of sacred events carried out at the celebration include preparation events in this case making snacks (snacks), accaramang (lectures), sibali-bali (dialogue between two children), and closed with mandre-andre (eating together). The values ​​of some of these events are sipatokkong (please help) based on QS al-Maidah/5: 2, sipakainge' (mutual reminder or da'wah) in QS al-Nahl/16: 125, and mandre-andre as a glue of friendship based (sibawa) on QS al-Hujurat/49: 10.